(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the key financial and institutional measures implemented by the United States to mitigate the socio-economic effects of the COVID-19 pandemic. The research focuses on how emergency fiscal stimulus programs, direct income support, and digital payment mechanisms redefined the nation’s social protection policy. Drawing on legislative frameworks such as the CARES Act (2020) and the American Rescue Plan (2021), the study analyzes their impact on poverty reduction, employment stabilization, and household income resilience. Using comparative and analytical methods, the paper highlights how the United States combined short-term relief with long-term social policy transformation. The findings demonstrate that rapid digitalization, fiscal inclusiveness, and data-driven decision-making were decisive factors in ensuring policy effectiveness. The U.S. experience reveals that during global crises, social protection must evolve beyond welfare assistance to function as a dynamic instrument of economic stabilization and social equity.